Chapitre V. Personnages féminins : entre rôle et représentation - Laurencin, Madeleine (Presses Sorbonne Nouvelle, 2018)
Vollmann’s Rifles, one of the Seven Dreams, is centered around the interaction between Inuits and the Western world, whether at the time of the Franklin expedition or in the contemporary world. The official (hi)story of the Inuit is here challenged, and rewritten with an emphasis on the human, and feminine, side of the events. Vollmann’s women, from Reepah to Lady Jane, are decisive yet changing, images of the ice sheets of the northern American continent.Although Vollmann’s narration is centered around tales of exploration, traditionally masculine, and presents Subzero and Franklin as two major members of a set of triplets, women permeate narration. Instead of naming them all, Vollmann enjoys presenting them as an amorphous group from which a few distinguish themselves: Reepah, Lady Jane Franklin and Sedna. Vollmann turns his female characters into mirrors of the men they interact with, yet the narrator is never able to pierce the mystery behind the mirror, leaving the reader to wonder at Reepah’s thought processin view of some of the conversations that she and Subzero have. The female characters are distinguished more by personality type than by physical aspect, an essential point for the novel. If the relationship Subzero has with Reepah is at times overly and overtly physical, he claims nonetheless to value above all her heart and spirit. In spite of the attempt made by the narrator to approach women indirectly, they remain nonetheless forever out of reach, strangers to him and to his fellow men.Yet if women remain outsiders throughout the narration, they are still at the core of the author’s writing. Vollmann works into The Rifles the trope of women as a territory, to be explored and conquered, just as the North-American continent was virgin territory at the time of Franklin’s expedition. The conquest, both on a personal and a national level, is transcribed in the novel through the use of language, and the discordant note of Reepah’s voice becomes a way for Vollmann to show how badly the Inuits have ...